2007 22nd International Congress on Instrumentation in Aerospace Simulation Facilities 2007
DOI: 10.1109/iciasf.2007.4380885
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bi-Luminophore Pressure-Sensitive Paint Systems

Abstract: Bi-luminophore Pressure-Sensitive Paint (bi-PSP) has been developed in order to correct the error due to temperature dependence of PSP and increase PSP measurement accuracy. The bi-PSP was composed of pressure-and temperature-sensitive dye. Tetranuclear europium (III) complexes and PdTFPP were used as temperature-and pressure-sensitive dye, respectively. The luminescence intensity of the Eu complex was highly sensitive to temperature and insensitive to pressure. The bi-PSP was examined using a painted coupon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Mixing two luminophores accelerated the photodegradation of the tetranuclear Eu(III) complex under the air atmosphere as reported in the previous studies by Mitsuo et al [ 40 ] and Mochizuki et al [ 41 ]. They used PdTFPP, a palladium porphyrin, as a pressure sensor and poly-IBM-co-TFEM as a binder.…”
Section: Results and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Mixing two luminophores accelerated the photodegradation of the tetranuclear Eu(III) complex under the air atmosphere as reported in the previous studies by Mitsuo et al [ 40 ] and Mochizuki et al [ 41 ]. They used PdTFPP, a palladium porphyrin, as a pressure sensor and poly-IBM-co-TFEM as a binder.…”
Section: Results and Discussionsupporting
confidence: 72%
“…Table 3 compares the present study with those two previous studies by focusing on the degradation rate of the temperature sensor. Mitsuo et al [ 40 ] did not provide the specific value of the degradation rate. Because Mochizuki et al [ 41 ] performed their aging test for only 30 min, the degradation rates at 30 min are shown in the table.…”
Section: Results and Discussionmentioning
confidence: 99%
“…From the point of view of the measurement procedure, Bell et al 8) , Mitsuo et al 7,9) , Yamashita et al 12) and Asai et al 13) reported the modification of the image acquisition procedure in PSP measurements by means of the intensity method. Especially, it is well known that a significant temperature change between reference (wind-off) -and run (wind-on) data is a major source of error.…”
Section: Introductionmentioning
confidence: 98%
“…Especially at low speed testing, high accurate PSP measurements are hardly possible without temperature correction because the change of the luminescence intensity by the pressure change is almost the same magnitude with that by a temperature change of a few degrees. To increase the accuracy of PSP measurement, researchers have developed low temperature-dependent dyes and polymers for PSP [1][2] and temperature-correction method with an infrared camera 3) or Temperature-Sensitive Paint (TSP) [4][5][6][7][8][9] . Furthermore, Yorita et al 10) and Matsuda et al 11) .…”
Section: Introductionmentioning
confidence: 99%
“…However, this symmetrical painting cannot be applied to an asymmetric flow field. Since most actual flow fields are asymmetric, the following three methods have been developed in which PSP and TSP measurements are applied to the same place: biluminophore paint [9][10][11][12][13][14], multilayer paint [15,16], and dotarray [17][18][19][20][21] sensors.…”
Section: Introductionmentioning
confidence: 99%